"Efectividad de un programa educativo en el conocimiento materno sobre cuidados del recién nacido" - Quispe Valencia, Loraine Esther (2017)
Quantitative, pre-experimental research; The objective was to establish the effectiveness of the "Love my baby" educational program at the maternal level of knowledge about newborn care at the Saint Lucía of Moche Health Center; The sample universe consisted of 20 first parities that were applied as Pretest and Postest, the Scale to determine the level of maternal knowledge about newborn care, elaborated by Chunga (2002) and modified by Quispe and Rosales (2016). The student came to the following conclusions: Before the implementation of the educational program, 75 percent of primary schools had a regular level of knowledge, 15 percent a good level and 10 percent. A Bad Level After implementation of the educational program, 100 percent of primiparas gained a good level of knowledge. The educational program was effective and the primaries were able to increase their level of knowledge more than 50 percent, obtaining a value for the student of -9,200 with probability 0.000 being highly significant.